Internet membership kit - Fraase, Michael; Hahn, Harley, 1952-.; Ventana Media (Firm) (Chapel Hill, NC : Ventana Media, 1994)
Allows Macintosh users to navigate the Internet using a graphical interface. Provides electronic mail, file transfer, and Telnet functions. Includes one-month CERFnet membership with six hours free online access, and two guidebooks entitled The Mac Internet tour guide and The Internet yellow pages.
Title from container.
System requirements: Macintosh Plus or greater; 4MB RAM; System 7.0 or later; high-density floppy disk drive; hard disk; 9600 baud modem (14,400 or 28,800 baud highly recommended); hardware handshaking modem cable; Internet account; SLIP or PPP connection.
Keywords: Internet -- Software